Rural development in large development projects: The case of compensation in Bakun Hydroelectric Dam Project - Lee, Wen Chiat; Viswanathan, K. Kuperan; Ali, Jamal (2013)
Compensation for indigenous communities as a result of rural development projects has been a controversial subject.The elements of rights, entitlements, freedoms and justice are often difficult to value. Most of the compensation packages given to the indigenous communities are in market values and non-market values are often ignored.The non-market values which are the social and cultural impacts are very difficult to determine and often not compensated by government.These non-market values are more important compared with market values to the indigenous communities. This paper identifies the reasons why there are conflicts between the policymakers (government) and indigenous communities in terms of valuing compensation by reviewing the empirical literature on economic and social impacts on indigenous communities resulting from relocation. The literature on different valuation methods is reviewed to understand the gaps between the policymakers and indigenous communities on compensation issues